Avaliação de Algoritmos de Aprendizado de Máquina para Predição de QoE em Redes 6G - Silva, Felipe S. Dantas; Lima, Mathews; Santos, Charles H. F.; Neto, Augusto (Anais do Workshop de Redes 6G (W6G), 2023)
This paper evaluates the performance of Machine Learning (ML) algorithms to provide Quality of Experience (QoE) user decisions in multimedia services. A specialized dataset was built for mapping network Quality of Service (QoS) Key Performance Indicators (KPIs) with video quality metrics to perform QoE predictions. An evaluation is then carried out considering the main regression models to support the development of QoE-aware systems and meet the critical requirements of applications characteristic of 6G scenarios.